Competitive strategy and profitability of peruvian companies that export cotton t-shirts - Lara Hidalgo, Carol Rocío (2019)
Objective: Infer the elements of the competitive strategy that affect the profitability of the cotton t-shirt Peruvian exporting companies. Method: The research method is correlational when trying to identify and formulate existing relationships between the proposed variables based on historical data and obtained data from surveys of 144 cotton t-shirt Peruvian exporting companies. For the analysis and processing data, simple linear correlation techniques, Pearson, Spearman and Chi Squared were used. The Programs Microsoft Excel e IBM SPSS used were. Primary (survey and financial statements) and second (government statistics, thesis and scientific articles) information was used. Results: It determine that exists a direct correlation between costs and expenses with company sales, this same case presents between the national exports and ROE, likewise, it evidence a direct relationship between cotton t-shirt prices and exports. The design is other component that has a direct impact on the profitability of the company. Conclusions: Exist a close relationship between indicators by the use of the Strategy of Leadership in Costs and Strategy of Differentiation that influence the profitability in exporting companies.